SAT0015 Novel and Rare Mutations Linked To Polyautoimmunity. (15th July 2016) - Johar, A.; Sarmiento-Monroy, J.C.; Rojas-Villarraga, A.; Silva-Lara, M.F.; Patel, H.R.; Mantilla, R.D.; Mastronardi, C.; Arcos-Burgos, M.; Anaya, J.-M.
Abstract : Background: Polyautoimmunity (i.e., the presence of two or more autoimmune diseases in a single patient) and familial autoimmunity (i.e., diverse autoimmune diseases in a nuclear family) represent extreme phenotypes ideal for identifying major genomic variants contributing to autoimmunity (1–3). Whole Exome Sequencing (WES) and linkage analysis are well suited for this purpose due to its strong resolution upon familial segregation patterns of functional protein coding and splice variants (3). Objectives: The primary objective of this study was to identify potentially autoimmune causative variants using WES data from extreme pedigrees segregating polyautoimmunity phenotypes. Methods: DNA of 47 individuals across 10 extended and multigenerational pedigrees, ascertained from probands affected with polyautoimmunity and familial autoimmunity, were selected for WES. Variant calls were obtained through Genome Alignment Tool Kit (GATK) algorithm; filters for prioritizing major functional were applied and later implemented for genetic linkage analysis. Sanger sequencing corroborated variants with significant linkage. Results: Novel and mostly rare variants harbored in SRA1, MLL4, ABCB8, DHX34 and PLAUR genes showed significant linkage (LOD scores are >3.30). The strongest signal was in SRA1, with a LOD score of 5.48. Network analyses indicated that SRA1 and PLAUR both contribute to regulation of apoptotic processes. Conclusions: Novel and rare variants in genetic linkage with polyautoimmunity were identified throughout WES. Genes harboring these variants might be major players of autoimmunity. References: Expert Rev Clin Immunol. 2007;3:623–35. BMC Med. 2013;11:73. Autoimmun Rev. 2015;14:204–9. Acknowledgement: Supported by Colciencias (Bogota, Colombia) Disclosure of Interest: None declared